2009
DOI: 10.1111/j.1464-5491.2009.02760.x
|View full text |Cite
|
Sign up to set email alerts
|

Neuropad as a diagnostic tool for diabetic autonomic and sensorimotor neuropathy

Abstract: Neuropad is a reliable diagnostic tool for both CAN and DPN, albeit of only moderate accuracy. Extending the observation period to 15 min provides greater diagnostic usefulness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
53
4
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 25 publications
12
53
4
2
Order By: Relevance
“…We found high sensitivity and negative predictive value of the Neuropad at 10 min, in concordance with previous studies [13,14,20,21,[28][29][30][31][32]. Although sensitivity and negative predictive value seemed slightly higher in the subgroup with peripheral arterial occlusive disease than without, differences were not significant.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…We found high sensitivity and negative predictive value of the Neuropad at 10 min, in concordance with previous studies [13,14,20,21,[28][29][30][31][32]. Although sensitivity and negative predictive value seemed slightly higher in the subgroup with peripheral arterial occlusive disease than without, differences were not significant.…”
Section: Discussionsupporting
confidence: 92%
“…Positive predictive value seemed also generally poorer in our study than in previous works [13,14,20,21,[28][29][30][31][32]; unlike specificity, it was significantly higher in subjects with peripheral arterial occlusive disease than without, which may be explained by the higher prevalence of peripheral neuropathy among these patients.…”
Section: Discussioncontrasting
confidence: 83%
“…Interestingly, NEURO-PAD™ has higher sensitivity and specificity for detecting peripheral neuropathy than milder forms of cardiac autonomic neuropathy using the standardized test proposed by Ewing [44]. This could be due to the fact that NEURO-PAD™ and cardiovascular tests explore different autonomic areas (cardiovascular autonomic neuropathy vs distal autonomic neuropathy) [47]. Spallone et al [47] found that evaluation of the test after 15 min of application provided a better balance between sensitivity (80%) and specificity (61%) in diagnosing both peripheral and autonomic neuropathy.…”
Section: Sudomotor Function Screening Testsmentioning
confidence: 93%
“…This could be due to the fact that NEURO-PAD™ and cardiovascular tests explore different autonomic areas (cardiovascular autonomic neuropathy vs distal autonomic neuropathy) [47]. Spallone et al [47] found that evaluation of the test after 15 min of application provided a better balance between sensitivity (80%) and specificity (61%) in diagnosing both peripheral and autonomic neuropathy.…”
Section: Sudomotor Function Screening Testsmentioning
confidence: 98%
See 1 more Smart Citation